2021
DOI: 10.3389/fnut.2021.595756
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Profile Is Associated With Residential Settings and Not Nutritional Status in Adults in Karnataka, India

Abstract: Undernutrition is a leading contributor to disease and disability in people of all ages. Several studies have reported significant association between nutritional status and gut microbiome composition but other factors such as demographic settings may also influence the adult microbiome. The relationship between undernourishment and gut microbiome in adults has not been described to date. In this study, we compared the gut microbiome in fecal samples of 48 individuals, from two demographic settings (rural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 74 publications
(83 reference statements)
1
0
0
Order By: Relevance
“…The alpha and beta diversity of the gut microbiota of women from Pemba and Unguja differ according to location even though they are ethnically close. This agrees with the study by Mehta et al, which demonstrated that residence location was associated with differences in gut microbiome composition in Indian adults [39]. This difference can be explained by the possible influence of the environment [40], more rural in one case, or the difference in their diets [13].…”
Section: Discussionsupporting
confidence: 92%
“…The alpha and beta diversity of the gut microbiota of women from Pemba and Unguja differ according to location even though they are ethnically close. This agrees with the study by Mehta et al, which demonstrated that residence location was associated with differences in gut microbiome composition in Indian adults [39]. This difference can be explained by the possible influence of the environment [40], more rural in one case, or the difference in their diets [13].…”
Section: Discussionsupporting
confidence: 92%